Edukasi Pentingnya Pemerikasaan Payudara Sendiri (SADARI) Bagi Wanita Usia Subur - Erin Rizkiana; Arlina Azka (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2023)
In Indonesia, the rate of delayed early detection of breast cancer is still high, reaching 80% and most of them are found in an advanced stage. One of the effective early screening methods recommended by the American Cancer Association in detecting breast cancer is Breast Self-Examination (BSE). This activity aims to increase awareness and knowledge of women of childbearing age about breast cancer and the importance of performing BSE to prevent or early detection of breast cancer. This activity was carried out using lecture, discussion, demonstration and simulation methods. Then an evaluation was carried out in the form of giving question in the form of questionnaires about knowledge of breast cancer and BSE. The results showed that the knowledge of women of childbearing age about breast cancer and BSE after education was mostly in the good category. This activity can affect the level of knowledge of women of childbearing age and is expected to improve their behavior and attitudes in BSE as prevention and early detection of breast cancer.